A Potential Mechanism of Temozolomide Resistance in Glioma–Ferroptosis - Hu, Zhifang; Mi, Yajing; Qian, Huiming; Guo, Na; Yan, Aili; Zhang, Yuelin; Gao, Xingchun (Frontiers in Oncology, 2020)
Temozolomide (TMZ) is the first-line chemotherapy drug that has been used to treat glioma for over a decade, but the benefits are limited by half of the treated patients who acquired resistance. Studies have shown that glioma TMZ resistance is a complex process with multiple factors, which has not been fully elucidated. Ferroptosis, which is a new type of cell death discovered in recent years, has been reported to play an important role in tumor drug resistance. The present study reviews the relationship between ferroptosis and glioma TMZ resistance, and highlights the role of ferroptosis in glioma TMZ resistance. Finally, the investigators discussed the future orientation for ferroptosis in glioma TMZ resistance, in order to promote the clinical use of ferroptosis induction in glioma treatment.